2015
DOI: 10.1016/j.febslet.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Double stranded promoter region of BRAF undergoes to structural rearrangement in nearly physiological conditions

Abstract: The folding of oncogene promoters into non-canonical DNA secondary structures is considered a strategy to control gene expression. Herein, we focused on a 30 bases sequence located upstream of the transcription start site of BRAF (Braf-176) that contains 80% of guanines. We analyzed the structural behavior of the G- and C-rich strands. By the use of spectroscopic and electrophoretic techniques we confirmed that they actually fold into a predominant antiparallel G-quadruplex and into an i-motif, respectively, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…A small stabilization is also observed for the i-motif structure formed by the complementary SMC03 sequence, which hardly melts at these conditions in pure aqueous media. Overall, this tendency agrees with previous reported works where it was shown that Hoogsteen base pairs are stabilized in the presence of PEG200 32,36 . On the contrary, the thermal stability of the Watson-Crick duplex formed by the mixture of the two sequences was reduced, a fact that also agreed with previous reports 37 .…”
Section: Resultssupporting
confidence: 93%
“…A small stabilization is also observed for the i-motif structure formed by the complementary SMC03 sequence, which hardly melts at these conditions in pure aqueous media. Overall, this tendency agrees with previous reported works where it was shown that Hoogsteen base pairs are stabilized in the presence of PEG200 32,36 . On the contrary, the thermal stability of the Watson-Crick duplex formed by the mixture of the two sequences was reduced, a fact that also agreed with previous reports 37 .…”
Section: Resultssupporting
confidence: 93%
“…There are two main G- and C-rich segments in the promoter region of this gene. One called B-raf is located downstream of the transcription start site and other called B-raf-176 found upstream of the start site at −176 position …”
Section: Resultsmentioning
confidence: 99%
“…In a number of instances the sequences are within established nuclease hypersensitive/transcriptional activation sites within or upstream of promoter regions. Well-studied examples of genes containing such quadruplex sites for which quadruplex formation in vitro has been demonstrated include c- MYC , BCL -2, , h- RAS , k- RAS , c- KIT , , HIF , , b- RAF , , the androgen receptor, RET , , HSP90 , MET , and VEGF, whereas promoter quadruplexes appear to under-represented in genes associated with normal cellular processes. Many validated and putative promoter quadruplexes tend to be within 1 kb, more commonly immediately upstream and close to the transcription start site in these genes.…”
Section: Promoter Quadruplexesmentioning
confidence: 99%